Design of Electric Power System for Xinhangcheng Station on Intercity Railway Connecting Line. Issue 1 (1st December 2022) - Yu, Guo
Abstract: At present, the intercity railway station is getting bigger and bigger, represented by the Intercity Railway Xinhangcheng Station. Xinhangcheng Station of the Intercity Railway Link Line is a key station for the national railway underground passenger transport, the scale of the building is larger than that of ordinary subway stations, with a total of 6 floors, including communication, signal, information, escalator, screen door and other equipment. The layout and design of ventilation, water supply, and fire-fighting equipment are more complicated than subways. The station also includes areas related to station support and integrated development, therefore, new requirements are put forward for the design of the station power system. Therefore, it is very important to study a reasonable and feasible power design scheme. In this paper, to meet the needs of the intercity railway tie line underground station building, station supporting and integrated development of electricity consumption and electricity consumption independent of each other, a 10KV/0.4KV substation is set up on the ground floor and on the second floor of the station building to supply power to the station, a 10KV/0.4KV substation is set up on the east and west sides of the supporting area to supply power to the municipal supporting area, and integrated development of a 10KV/0.4KV substation is set up to supply power for integrated commercial development, meeting the needs of all parties.